Antimicrobial Photodynamic Therapy (Apdt), An Approach To Fightback Against Antibiotic Resistance: A Short Review (Stamford Journal of Microbiology, 2023)
Antimicrobial photodynamic therapy (APDT), a novel tool for combating the drug resistant microorganisms which is combined with modern technologies and tools. The versatile and wide range of available photosensitizers (PS) and different wavelength light combinations opened so many ways to kill potential disease-causing pathogens. The research is developing so fast with the help of photochemistry, photobiology and photophysics. This is the beginning of new era of another antimicrobial solutions compared to conventional antibiotics. Many articles have published regarding studies on APDT and its applications. This method has shown successful eliminations of pathogenic microorganisms in skin, dental and foot infections as well as tumor or cancer treatment. The findings shared the knowledge of safe and resistance free alternative treatment of antibiotics which has clinical importance globally. This review highlights the concept, history, mechanisms, applications and the advantages of APDT.Stamford Journal of Microbiology, 2023. Vol. 13, Issue 1, p. 30-37